If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(4c-5)=2(6c+12)
We move all terms to the left:
4(4c-5)-(2(6c+12))=0
We multiply parentheses
16c-(2(6c+12))-20=0
We calculate terms in parentheses: -(2(6c+12)), so:We get rid of parentheses
2(6c+12)
We multiply parentheses
12c+24
Back to the equation:
-(12c+24)
16c-12c-24-20=0
We add all the numbers together, and all the variables
4c-44=0
We move all terms containing c to the left, all other terms to the right
4c=44
c=44/4
c=11
| 7x−5=30 | | 14+6h=38 | | 2.80(g)=20 | | 20000x+8x=50000x+5x | | 3x+6(x-2)=15 | | /c=18 | | 3x+6(x-2)=17 | | `1-8n=33 | | 3+7b=38 | | 7x-52/4=17x | | 0.25(x+12)=30 | | 0.75x=1.3 | | 3x+-8=26 | | -7x+2=-4x+7 | | 5 | | 32=–3x–1 | | b4+ –9=–13 | | 13+3v=-20 | | –a+104=0 | | 21=3(v+8) | | 5x–9=5x+19 | | 13+3v=-0 | | 7x-3=2x+7 | | |y=-1 | | 3/4(y+1)=-6 | | 16.67x-1=0 | | 3/2(x-1/3)-x+1/3(3x-6)=3/2(x+1/3) | | 2x-7+5x+3+x=180 | | 3(4x+2)=5(3+3x) | | z+12=8 | | –2(v+12)=–12 | | -2x-2(-5x+13)=14 |